A lithium iron phosphate positive electrode material and its preparation method and application

By adjusting the grain size and b-axis length of the lithium iron phosphate positive electrode material, combined with the use of dopants and fluxes, a lithium iron phosphate positive electrode material with K≤1 was prepared, which solved the problem of poor conductivity and achieved high conductivity and high capacity effects.

CN117691064BActive Publication Date: 2025-02-25SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311615121.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2025-02-25
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

The current lithium iron phosphate positive electrode materials have poor electrical conductivity, which affects the electrical performance of the battery.

Method used

By adjusting the grain size and b-axis length of the lithium iron phosphate positive electrode material, K≤1 is ensured, and combined with the use of dopants and fluxes, lithium iron phosphate positive electrode material with high conductivity and low resistivity is prepared.

Benefits of technology

The high conductivity, low resistivity, high compaction density and high capacity of lithium iron phosphate positive electrode material are achieved, and the overall electrical performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117691064B_ABST
    Figure CN117691064B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of electrode material preparation, and specifically relates to a lithium iron phosphate positive electrode material, a preparation method and an application thereof. The K value of the lithium iron phosphate positive electrode material is ≤1, and K is calculated by the grain size and b-axis length of the lithium iron phosphate positive electrode material. The positive electrode material has excellent properties such as low resistivity, high conductivity, high compaction density and high capacity. The inventor found in the research process that the lithium iron phosphate positive electrode material K≤1 can ensure that it has excellent properties such as high conductivity, low resistivity, high compaction density and high capacity. The powder resistivity of the lithium iron phosphate positive electrode material is less than 10Ω·cm, and the compaction density is greater than 2.2g / cm 3 , 0.1C discharge capacity is greater than 160mAh / g, 1C discharge capacity is greater than 150mAh / g, it has the advantage of high capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode material preparation, and in particular relates to a lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate (LiFePO4) has become one of the most widely used positive electrode materials for lithium-ion batteries due to its advantages such as low cost, stable charging and discharging platform, environmental friendliness and high safety. At present, the domestic shipment volume of lithium iron phosphate has exceeded that of ternary lithium phosphate, but the conductivity of the material has always been an urgent problem to be solved in the industry, as the conductivity of the material directly affects the electrical performance of the battery. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the lithium iron phosphate positive electrode material in the prior art, such as poor conductivity, so as to provide a lithium iron phosphate positive electrode material and a preparation method and application thereof.

[0004] To this end, the present invention provides the following technical solutions.

[0005] A first aspect of the present invention provides a lithium iron phosphate positive electrode material, wherein K of the lithium iron phosphate positive electrode material is less than or equal to 1, and K satisfies the relation 1:

[0006] K=D+(b-6)×100 Relationship 1

[0007] D is the grain size of lithium iron phosphate positive electrode material, 0.05μm≤D≤0.15μm;

[0008] b is the b-axis length of the lithium iron phosphate positive electrode material,

[0009] A second aspect of the present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0010] (1) mixing iron phosphate, a lithium source, a dopant, a carbon source and a flux and grinding the mixture to obtain a slurry;

[0011] The iron-phosphorus ratio of the ferric phosphate is 0.975-0.99, and the specific surface area is 6-10m 2 / g; the particle size D50 of the slurry is 300-500nm; the doping elements in the dopant include at least two of vanadium, titanium, tungsten and magnesium; the mass content of the doping elements in the lithium iron phosphate positive electrode material is 1000-5000ppm; the flux is at least one of lithium fluoride, lithium phosphate and lithium dihydrogen phosphate;

[0012] (2) drying and sintering the slurry to obtain a lithium iron phosphate positive electrode material with K≤1;

[0013] Where, K = D + (b-6) × 100, equation 1

[0014] D is the grain size of lithium iron phosphate positive electrode material, 0.05μm≤D≤0.15μm;

[0015] b is the b-axis length of the lithium iron phosphate positive electrode material,

[0016] When using XRD to determine the grain size D and b-axis length of lithium iron phosphate cathode materials, it is necessary to ensure that R wp ≤10%, R wp It is the residual variance factor of the weighted graph, which can ensure the accuracy of refinement.

[0017] The molar ratio of the iron phosphate to the lithium in the flux is 1:(0.02-0.06).

[0018] The dopant includes at least two of vanadium pentoxide, titanium dioxide, tungsten trioxide and magnesium oxide.

[0019] When the dopant includes at least two of vanadium pentoxide, titanium dioxide, tungsten trioxide and magnesium oxide, the mass ratio of different dopants is not specifically limited. When the dopant includes two of vanadium pentoxide, titanium dioxide, tungsten trioxide and magnesium oxide, the mass ratio can be but not limited to 1:1, 1:2, 1:3, 2:1, 2:5, etc.; when the dopant includes three of vanadium pentoxide, titanium dioxide, tungsten trioxide and magnesium oxide, the mass ratio can be but not limited to 3:2:1, 4:3:1, 1:1:1, 2:1:1, 2:5:3, 5:10:7, etc.; when the dopant includes four of vanadium pentoxide, titanium dioxide, tungsten trioxide and magnesium oxide, the mass ratio can be but not limited to any value such as 4:3:2:1, 7:7:6:4, 1:3:1:1, 1:1:1:1, 2:5:7:10, 5:10:15:6, etc.

[0020] The mass content of carbon element in the lithium iron phosphate positive electrode material is 1.3-1.5wt%;

[0021] Preferably, the carbon source is at least one of polyethylene glycol, glucose, carbon nanotubes, sucrose and starch.

[0022] When the carbon sources include two or more, the mass ratio of different carbon sources is not specifically limited. When the carbon sources include two, the mass ratio of the two carbon sources can be but is not limited to 2:1, 3:2, 1:1, 2:7, 8:3, etc.; when the carbon sources include three, the mass ratio of the three carbon sources can be but is not limited to 2:1:1, 3:2:7, 1:1:1, 2:7:6, 8:3:5, etc.; when the carbon sources include four, the mass ratio of the four carbon sources can be but is not limited to 2:1:1:6, 3:2:7:1, 1:1:1:9, 2:7:6:6, 8:3:5:2, etc.; when the carbon sources include five, the mass ratio of the five carbon sources can be but is not limited to 2:1:1:6:7, 3:2:7:1:4, 1:1:1:9:1, 2:7:6:6, 8:3:5:2:1, etc.

[0023] The preparation method satisfies at least one of (1) to (3):

[0024] (1) The lithium source is lithium carbonate and / or lithium hydroxide monohydrate;

[0025] (2) The molar ratio of the iron phosphate to the lithium in the lithium source is 1:(0.97-1.02);

[0026] (3) The mass content of water in the slurry is 50-70%.

[0027] The drying is spray drying;

[0028] Preferably, the spray drying parameters are: feed frequency is 10-30 Hz, atomizer frequency is 40-60 Hz;

[0029] Preferably, the temperature of the inlet air is 240-270°C;

[0030] Preferably, the outlet air temperature is 80-100°C.

[0031] The specific steps of sintering include: heating to 750-820° C. at a heating rate of 1.5-4° C. / min and then keeping the temperature for 8-12 hours.

[0032] A third aspect of the present invention provides a pole piece, comprising a current collector and a coating attached to the current collector; the raw material of the coating comprises the above-mentioned lithium iron phosphate positive electrode material or the lithium iron phosphate positive electrode material prepared by the above-mentioned preparation method.

[0033] A fourth aspect of the present invention provides a battery, comprising the above-mentioned lithium iron phosphate positive electrode material, the lithium iron phosphate positive electrode material prepared by the above-mentioned preparation method, or the above-mentioned electrode sheet.

[0034] The technical solution of the present invention has the following advantages:

[0035] 1. The lithium iron phosphate positive electrode material provided by the present invention has a K value of ≤1, K is calculated by the grain size and b-axis length of the lithium iron phosphate positive electrode material, and the positive electrode material has excellent properties such as low resistivity, high conductivity, high compaction density, and high capacity. The inventors found in the research process that the lithium iron phosphate positive electrode material K≤1 can ensure that it has excellent properties such as high conductivity, low resistivity, high compaction density, and high capacity. The powder resistivity of the lithium iron phosphate positive electrode material is less than 10Ω·cm, and the compaction density is greater than 2.2g / cm 3 , 0.1C discharge capacity is greater than 160mAh / g, 1C discharge capacity is greater than 150mAh / g, it has the advantage of high capacity.

[0036] 2. The preparation method of the lithium iron phosphate positive electrode material provided by the present invention can produce a lithium iron phosphate positive electrode material with good comprehensive properties such as low resistivity, high conductivity, high compaction density, and high capacity. The powder resistivity of the lithium iron phosphate positive electrode material produced by the present invention is less than 10Ω·cm, and the compaction density is greater than 2.2g / cm 3 , 0.1C discharge capacity is greater than 160mAh / g, 1C discharge capacity is greater than 150mAh / g, and has the advantage of high capacity. The present invention obtains K≤1 lithium iron phosphate positive electrode material by controlling the iron-phosphorus ratio, specific surface area, slurry particle size, amount of doping elements and type of flux of iron phosphate. The lithium iron phosphate positive electrode material with K≤1 has comprehensive properties such as low resistivity, high conductivity, high compaction density and high capacity.

[0037] Lithium iron phosphate has a one-dimensional lithium ion transmission channel, and lithium ions are transmitted along the b-axis. The shorter the b-axis, the faster the lithium ion transmission, the better the ion conductivity, and the smaller the grain size, the higher the capacity. During the research, the inventor found that the lithium iron phosphate positive electrode material K≤1 can ensure that it has excellent properties such as high conductivity and low resistivity. Furthermore, the method of the present invention can make the lithium iron phosphate positive electrode material K≤1, thereby improving its conductivity and capacity and other properties.

[0038] 3. The method for preparing the lithium iron phosphate positive electrode material provided by the present invention can further optimize the conductivity by adjusting the amount of the co-solvent when preparing the lithium iron phosphate positive electrode material.

[0039] The present invention further optimizes the type of carbon source to ensure the carbon content in the lithium iron phosphate positive electrode material product; the spherical size and moisture content of the dried material can be controlled by optimizing the spray drying parameters. For example, if the feeding frequency is too fast, the material particles are large and the moisture content is high; if the atomizer frequency is too low, the particles are large, which is not conducive to the improvement of compaction density and the subsequent process; the present invention optimizes the air inlet temperature and the air outlet temperature to facilitate the discharge of moisture, and will not generate high energy consumption, cause carbon volatilization, and affect the carbon content of the product. When preparing the lithium iron phosphate positive electrode material, the present invention can further improve its electrical properties by controlling the sintering temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 It is a scanning electron microscope image of the lithium iron phosphate positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0042] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0043] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0044] In a specific embodiment, the molecular formula of iron phosphate can be represented by Fe x PO4, wherein the value range of x is 0.975-0.99, ensuring that the iron-phosphorus ratio of the iron phosphate is 0.975-0.99. In each embodiment, the molecular weight of the iron phosphate can be calculated by 55.85x+31+16×4.

[0045] Example 1

[0046] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0047] (1) With an iron-phosphorus ratio of 0.982 and a specific surface area of ​​8.1 m2 / g of anhydrous ferric phosphate was used as a raw material, and it was mixed with lithium carbonate, titanium dioxide, vanadium pentoxide, polyethylene glycol, sucrose, lithium phosphate, and water in a mass ratio of 100:24.1:0.42:0.36:8:2:0.8:206.64, stirred for 30 minutes and then ground to obtain a slurry with a particle size D50 of 356nm.

[0048] (2) The slurry is spray dried at a feed frequency of 26 Hz, an atomizer frequency of 48 Hz, an air inlet temperature of 260°C, and an air outlet temperature of 85°C; the sprayed dry material is then sintered, heated to 785°C at a heating rate of 3°C / min, and kept warm for 10 hours, and then pulverized by air flow to obtain a lithium iron phosphate positive electrode material satisfying K≤1. The K value of the lithium iron phosphate positive electrode material is calculated by equation 1.

[0049] Example 2

[0050] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material. The difference from Embodiment 1 is that the iron-phosphorus ratio of anhydrous iron phosphate is changed. The iron-phosphorus ratio of anhydrous iron phosphate in this embodiment is 0.976. The rest is the same as Embodiment 1.

[0051] Example 3

[0052] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, which differs from Embodiment 1 in that tungsten trioxide is used instead of vanadium pentoxide, and the mass ratio of iron phosphate, lithium carbonate, titanium dioxide, tungsten trioxide, polyethylene glycol, sucrose, lithium phosphate, and water is 100:24.1:0.42:0.26:8:2:0.8:206.64, and the rest is the same as Embodiment 1.

[0053] Example 4

[0054] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material. The difference from Embodiment 1 is that the sintering temperature is changed. The sintering temperature of this embodiment is 810° C., and the rest is the same as Embodiment 1.

[0055] Example 5

[0056] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0057] (1) With an iron-phosphorus ratio of 0.979 and a specific surface area of ​​6.5 m 2 / g of anhydrous ferric phosphate was used as a raw material, and it was mixed with lithium hydroxide monohydrate, tungsten trioxide, magnesium oxide, carbon nanotubes, starch, lithium fluoride, and water in a mass ratio of 100:27.6:0.13:0.52:8:2:0.8:206.64, stirred for 25 minutes and then ground to obtain a slurry with a particle size D50 of 472nm.

[0058] (2) The slurry is spray dried at a feed frequency of 15 Hz, an atomizer frequency of 55 Hz, an air inlet temperature of 260°C, and an air outlet temperature of 85°C; the sprayed dry material is then sintered, heated to 755°C at a heating rate of 2.5°C / min, and kept warm for 9 hours, and then air flow crushed to obtain a lithium iron phosphate positive electrode material satisfying K≤1. The K value of the lithium iron phosphate positive electrode material is calculated by equation 1.

[0059] Comparative Example 1

[0060] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material. The difference from Example 1 is that the iron-phosphorus ratio of anhydrous iron phosphate is changed. The iron-phosphorus ratio of anhydrous iron phosphate in this comparative example is 0.965, and the rest is the same as Example 1.

[0061] Comparative Example 2

[0062] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, which is different from Example 1 in that the amount of titanium dioxide added is changed to 0.82, and the rest is the same as Example 1.

[0063] Comparative Example 3

[0064] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, which is different from Example 1 in that no flux is added (ie, no lithium phosphate is added), and the rest is the same as Example 1.

[0065] Test example

[0066] This test example provides performance tests of lithium iron phosphate positive electrode materials in various embodiments and comparative examples, specifically:

[0067] (1) The powder resistivity, compaction density, carbon content, and doping element content of the lithium iron phosphate positive electrode material were obtained by ICP testing method. The results are shown in Table 1.

[0068] The K value of the lithium iron phosphate positive electrode material of each embodiment and comparative example is calculated by equation 1, as shown in Table 1;

[0069] Where, K = D + (b-6) × 100 Relation 1

[0070] D is the grain size of lithium iron phosphate positive electrode material, 0.05≤D≤0.15um;

[0071] b is the b-axis length of the lithium iron phosphate positive electrode material,

[0072] D and b are obtained through XRD testing; when obtaining D and b values, it is necessary to ensure that R wp ≤10%, R wp is the residual variance factor of the weighted graph, which can ensure the accuracy of refinement.

[0073] (2) Preparation method of button half-cell: lithium iron phosphate positive electrode material (from each embodiment and comparative example), carbon black (SP), and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 90:5:5, N-methylpyrrolidone (NMP) was added, and the mixture was evenly coated on aluminum foil, dried at 100° C. for 4 h, cut into positive electrode sheets with a diameter of 12 mm, and assembled to obtain button half-cells. After standing for 12 h, the battery performance was tested. The results are shown in Table 1.

[0074] Battery capacity testing method: using Xinwei testing cabinet, 0.1C charging, cut-off voltage 3.75V, 0.1C discharging, cut-off voltage 2V, 0.5C charging, cut-off voltage 3.75V, 1C discharging, cut-off voltage 2V.

[0075] Table 1 Performance results of positive electrode materials in various embodiments and comparative examples

[0076]

[0077]

[0078] The above results show that the lithium iron phosphate positive electrode material with K≤1 of the present invention has good conductivity and low resistivity. The specific surface area of ​​the positive electrode material of the present invention is 11-14m 2 / g, carbon content is 1.3-1.5wt%, compaction density is greater than 2.2g / cm 3 Furthermore, the positive electrode material also has a higher discharge capacity.

[0079] Furthermore, when the iron-phosphorus ratio of iron phosphate in comparative example 1 is lower than 0.975, a lithium iron phosphate positive electrode material with K≤1 cannot be obtained; the mass content of the doped element in the lithium iron phosphate positive electrode material obtained in comparative example 2 is 7000ppm, and a lithium iron phosphate positive electrode material with K≤1 cannot be obtained; and after no flux is added in comparative example 3, a lithium iron phosphate positive electrode material with K≤1 cannot be obtained. The above results show that the present invention can obtain a lithium iron phosphate positive electrode material with K≤1 by controlling parameters such as the iron-phosphorus ratio of iron phosphate and the content of doped elements, thereby ensuring the conductivity and capacity of the positive electrode material, and also having a good compaction density.

[0080] (3) Figure 1 This is a scanning electron microscope image of the lithium iron phosphate cathode material obtained in Example 1 of the present invention at 50,000 times magnification. It can be seen from the figure that the particle size of the lithium iron phosphate cathode material is small, lithium ions are easy to be deintercalated, and the ion conductivity is good; it can also be seen from the figure that the conductive carbon layer is attached to the surface of the particles, which can further improve the electronic conductivity. It further illustrates that the lithium iron phosphate cathode material with K≤1 provided by the present invention has good conductivity.

[0081] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A lithium iron phosphate positive electrode material, characterized in that: The K of the lithium iron phosphate positive electrode material is less than or equal to 1, and K satisfies the relationship 1: K = D + (b-6) × 100 Relationship 1; D is the grain size of lithium iron phosphate positive electrode material, 0.05μm≤D≤0.15μm; b is the b-axis length of the lithium iron phosphate positive electrode material, ; The preparation method of the lithium iron phosphate positive electrode material comprises the following steps: (1) mixing iron phosphate, a lithium source, a dopant, a carbon source and a flux and grinding the mixture to obtain a slurry; The iron-phosphorus ratio of the ferric phosphate is 0.975-0.99, and the specific surface area is 6.5-10m 2 / g; the particle size D50 of the slurry is 300-500nm; the doping elements in the dopant include at least two of vanadium, titanium, tungsten and magnesium; the mass content of the doping elements in the lithium iron phosphate positive electrode material is 1000-5000ppm; the flux is at least one of lithium fluoride, lithium phosphate and lithium dihydrogen phosphate; (2) Drying and sintering the slurry to obtain a lithium iron phosphate positive electrode material with K≤1.

2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the iron phosphate to the lithium in the flux is 1:(0.02-0.06).

3. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The dopant includes at least two of vanadium pentoxide, titanium dioxide, tungsten trioxide and magnesium oxide.

4. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass content of carbon element in the lithium iron phosphate positive electrode material is 1.3-1.5wt%; And / or, the carbon source is at least one of polyethylene glycol, glucose, carbon nanotubes, sucrose and starch.

5. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: Satisfy at least one of (1)-(3): (1) The lithium source is lithium carbonate and / or lithium hydroxide monohydrate; (2) The molar ratio of the iron phosphate to the lithium in the lithium source is 1:(0.97-1.02); (3) The mass content of water in the slurry is 50-70%.

6. The lithium iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The drying is spray drying.

7. The lithium iron phosphate positive electrode material according to claim 6, characterized in that: The parameters of the spray drying are: feed frequency is 10-30 Hz, atomizer frequency is 40-60 Hz; The inlet air temperature is 240-270℃; The air outlet temperature is 80-100℃.

8. The lithium iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The specific steps of sintering include: heating to 750-820° C. at a heating rate of 1.5-4° C. / min and then keeping the temperature for 8-12 hours.

9. A pole piece, characterized in that: It comprises a current collector and a coating attached to the current collector; the raw material of the coating comprises the lithium iron phosphate positive electrode material according to any one of claims 1 to 8.

10. A battery, characterized in that: It comprises the lithium iron phosphate positive electrode material according to any one of claims 1 to 8 or the pole piece according to claim 9.

Citation Information

Patent Citations

  • Preparation method of lithium iron phosphate with high compaction density

    CN115092903A

  • Long-miscible-gap high-rate lithium iron phosphate material and preparation method thereof

    CN115215314A

Cited By

  • Lithium iron phosphate positive electrode material, preparation method therefor and use thereof

    EP4819227A1